Biosafety status analysis and risk assessment of laboratories from 2021 to 2023 in Jiaxing, China - Yan, Yong; Li, Chan; Xu, Jingyu; Gao, Lei; Jiang, Zhenggang; Lv, Shencong; Li, Ping; Xiang, Zelin; He, Peiyan; Ren, Ganglin; Zhu, Guoying; Chen, Zhongwen (Frontiers in Bioengineering and Biotechnology, 2025)
In order to understand the laboratory biosafety status of Jiaxing from 2021 to 2023, before and after the end of the COVID-19 strict control strategy, this study used Zhejiang local standard DB33/T 2540 to conduct biosafety quality control inspection and risk identification, and used Chinese industry standard RB/T 040 for risk analysis and assessment. The results showed that the major problems in biosafety management were from organization management, laboratory housekeeping, material and label management, and facilities and equipment, accounting for 39.76%, 28.97% and 14.69% respectively. Statistical analysis showed that the significant improvement of laboratory filing requirements (χ2 = 5.84, P = 0.016) was the main reason for the decrease of organization management problems (χ2 = 5.007, P = 0.025). The problems of laboratory housekeeping, experimental material and safety label management had become increasingly prominent (χ2 = 6.192, P = 0.013), especially the nonstandard use of biosafety label (χ2 = 5.218, P = 0.022). Assessment results showed that all found problems as identified risk factors in the past 3 years were determined at the level of medium or low. These suggested that in 2021–2023, the overall laboratory biosafety risk level in Jiaxing was controllable and acceptable, and the organization management had been improved greatly. At the same time, the management of laboratory housekeeping, materials and labels, especially the use of biosafety labels, had become increasingly prominent and need to be standardized and strengthened.